Industrial training report: PERKESO Seri Manjung / Siti Ili Syuhada Ahmad Zaid - Ahmad Zaid, Siti Ili Syuhada (Universiti Teknologi MARA, Perlis, 2021)
My six-month industrial training at SOCSO Seri Manjung was summarized in this report. My industrial training began on March 1, 2021, and will end on August 13, 2021 Puan Rossita Binti Ladin, my supervisor, and Encik Muhammad Ashreeq Bin Amierullah, a SOCSO’s officer who gave and shared a lot of information with me, were the person who supported me the most during my internship. I am assigned to five departments in this office which are the Benefit Department, the Enforcement Department, the Finance Department, the Administration Department, and the Employment Insurance System (EIS) Department. According to the schedule, I will rotate through each department once every two weeks. The goal of this exchange is to gain more knowledge and experience about this company. Furthermore, this report discusses SOCSO's company's industry analysis for eight consecutive years. This industry analysis seeks to assess the company's performance in several areas, including profitability ratio, leverage ratio, liquidity ratio, and efficiency ratio, to determine whether it is performing well or poorly. Other than that, it also discusses how to solve the company's problems to improve their performance.